2007
DOI: 10.1530/eje-07-0566
|View full text |Cite
|
Sign up to set email alerts
|

Reference range of serum calcitonin levels in humans: influence of calcitonin assays, sex, age, and cigarette smoking

Abstract: Objective: The objective of this study was to re-evaluate the adult C T reference values determined by five different immunoassays and by introducing criteria for selecting control subjects. Design: A prospective multicenter study. Patients: Three hundred and seventy-five clinically euthyroid subjects. Methods: We used five different C T immunoassays. Sera were assayed for the concentration of TSH, gastrin, procalcitonin, urea, calcium, and anti-thyroperoxidase antibodies. Results: Screening for the various po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 39 publications
8
80
0
11
Order By: Relevance
“…Basal median serum Ct as well as median calcitonin-AUC were higher in men when compared to women. These results are in agreement with the findings of d' Herbomez et al, 8 who reported that serum Ct levels are higher in normal men when compared to women. In the subgroup of participants in whom serum cortisol increased during GTT, serum Ct increased significantly by 42% at 30 min compared to an increase by 17% in the participants in whom serum cortisol decreased.…”
Section: Discussionsupporting
confidence: 93%
“…Basal median serum Ct as well as median calcitonin-AUC were higher in men when compared to women. These results are in agreement with the findings of d' Herbomez et al, 8 who reported that serum Ct levels are higher in normal men when compared to women. In the subgroup of participants in whom serum cortisol increased during GTT, serum Ct increased significantly by 42% at 30 min compared to an increase by 17% in the participants in whom serum cortisol decreased.…”
Section: Discussionsupporting
confidence: 93%
“…Calcitonin (CT) 12 is an extremely sensitive marker for both the initial diagnosis and follow-up of patients with medullary thyroid cancer (MTC) (1)(2)(3)(4)(5). Sandwich immunoassays are applied when measuring CT in the clinical laboratory.…”
Section: © 2010 American Association For Clinical Chemistrymentioning
confidence: 99%
“…In addition, different analytical, physiological, pharmacological and pathological factors may significantly reduce the specificity and overall accuracy of serum CT measurement 3. Due to the influence of these factors, there is a high variability in assay‐dependent and gender‐dependent cut‐offs used to discriminate between MTC, C‐cell hyperplasia (CCH) and healthy C cells 10. Additionally, CT is prone to in vitro decay at room temperature which makes rapid centrifugation and storage at −20°C of samples mandatory 11, 12…”
Section: Introductionmentioning
confidence: 99%